Gerakan Penghijauan: Penanaman Alpukat untuk Cegah Erosi dan Tingkatkan Nilai Ekonomi Desa Margajaya, Kabupaten Ciamis - Adila Awaludin; Rival Nurhamzah Alfarizi; Enur Syamsi; Laimma Marya Tunnisa; Gina Agnia; Rina Maryana (Journal of Empowerment Community, 2026)
Soil erosion in the Parangonan area is a primary concern, threatening land fertility and environmental balance. The available vacant land has great potential to be managed as a conservation effort that can also provide added value for the community. This activity aimed to utilize vacant land by planting trees as a concrete step to prevent erosion, while also greening the environment and creating a resource with sustainable economic value for the residents. The method used was participatory action, where the service team worked directly with the local community to plant avocado tree seedlings in the land provided by the village. A total of 15 avocado tree seedlings were successfully planted. The presence of these trees not only functions to bind the soil and prevent erosion but is also expected to become an economic asset for the community when they bear fruit, as avocados have a fairly high market value.